Stability and magnetic properties of isomorphous substituted Si7-xMnx+ - Mai, Nguyen Thi; Tung, Nguyen Thanh; Cuong, Ngo Tuan (Vietnam Journal of Science and Technology, 2018)
The optimized geometries, stability, and magnetic properties of cationic clusters Si7+, Si6Mn+, and Si5Mn2+ have been determined by the method of density functional theory using the B3P86/6-311+G(d) functional/basis set. Their electronic configurations have been analyzed to understand the influence of substituting Si atoms by Mn atoms on the structural and magnetic aspects of Si7+. It is shown that the manganese dopant does not alter the structure of the silicon host but significantly changes its stability and magnetism. In particular, while the magnetic moment of Si7+ is 1 mB, Si5Mn2+ exhibits a strong magnetic moment of 9 mB and that of Si6Mn+ takes a relatively high value of 4 mB. Among studied clusters, the pentagonal bipyramid Si5Mn2+ is assigned as the most stable one.